Effects of Boron and Carbon Added Titanium Filler on Microstructure and Mechanical Properties of Ti-15-3 Alloy Weldments - Adli Bin Mohd Arif, Izzul; Kumar Talari, Mahesh; Kishore Babu, N; Lutfi Bin Anis, Ahmad; Hussain Ismail, Muhammad; Bin Ramli, Rosmamuhamadani (International Journal of Engineering and Technology, 2019)
Microstructural and mechanical properties beta Titanium (Î²-Ti) weldments can be improved by grain refinement and formation of insoluble precipitates in the weld. This paper reports the effect of Boron (B) and Carbon (C) addition to Ti-15V-3Cr-3Sn-3Al (Ti-15-3) fillers on the microstructural and mechanical properties of Ti-15-3 gas tungsten arc weldments. X-ray diffraction and scanning electron microscopic analysis revealed the presence of Î²-Ti phase in the weldments prepared without the filler modification, while additional TiB and TiC phases are observed in the weldments prepared with fillers modified with B and C, respectively. B and C addition to the fillers has resulted in the grain refinement of the weldments and the grain size reduction is seen to be higher with the increasing B and C addition. The formation of TiB, TiC and growth restriction effect due to the presence of B and C in the filler resulted in the decreased grain size of the Î²-Ti weldments. Mechanical properties such as hardness and tensile strength improved as the amount of B and C addition increased. The improvement of mechanical properties is contributed by the grain refinement and the formation of TiB and TiC precipitates in weldments.Â